Facial Expression Related vMMN: Disentangling Emotional from Neutral Change Detection - Kovarski, Klara; Latinus, Marianne; Charpentier, Judith; Cléry, Helen; Roux, Sylvie; Houy-Durand, Emmanuelle; Saby, Agathe; Bonnet-Brilhault, Frédérique; Batty, Magali; Gomot, Marie (Frontiers in Human Neuroscience, 2017)
Detection of changes in facial emotional expressions is crucial to communicate and to rapidly and automatically process possible threats in the environment. Recent studies suggest that expression-related visual mismatch negativity (vMMN) reflects automatic processing of emotional changes. In the present study we used a controlled paradigm to investigate the specificity of emotional change-detection. In order to disentangle specific responses to emotional deviants from that of neutral deviants, we presented neutral expression as standard stimulus (p= 0.80) and both angry and neutral expressions as deviants (p= 0.10, each). In addition to an oddball sequence, an equiprobable sequence was presented, to control for refractoriness and low-level differences. Our results show that in an early time window (100-200ms), the controlled vMMN was greater than the oddball vMMN only for the angry deviant, suggesting the importance of controlling for refractoriness and stimulus physical features in emotion related studies. Within the controlled vMMN, angry and neutral deviants both elicited early and late peaks occurring at 140ms and 310ms, respectively, but only the emotional vMMN presented sustained amplitude after each peak. By directly comparing responses to emotional and neutral deviants, our study provides evidence of specific activity reflecting the automatic detection of emotional change. This differs from broader “visual” change processing, and suggests the involvement of two partially-distinct pre-attentional systems in the detection of changes in facial expressions.